2018
DOI: 10.1016/j.canep.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

EPHA2 sequence variants are associated with susceptibility to Kaposi’s sarcoma-associated herpesvirus infection and Kaposi’s sarcoma prevalence in HIV-infected patients

Abstract: Variations in the KSHV entry receptor gene EPHA2 affected susceptibility to KSHV infection and KS development in a South African HIV-infected patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Further, our results demonstrate that an RRV gL-null mutant can still elicit potent immune responses to a vectored antigen. In the light of recent findings that show an association between variants in the gene coding for the human EphA2 KSHV receptor and KSHV infection as well as development of Kaposi's sarcoma (42), our findings with an Eph-detargeted rhadinovirus mutant successfully vectoring an SIV antigen may have implications for the development of a live-attenuated KSHV vaccine or the use of live-attenuated KSHV as a vaccine vector.…”
Section: Discussionmentioning
confidence: 56%
“…Further, our results demonstrate that an RRV gL-null mutant can still elicit potent immune responses to a vectored antigen. In the light of recent findings that show an association between variants in the gene coding for the human EphA2 KSHV receptor and KSHV infection as well as development of Kaposi's sarcoma (42), our findings with an Eph-detargeted rhadinovirus mutant successfully vectoring an SIV antigen may have implications for the development of a live-attenuated KSHV vaccine or the use of live-attenuated KSHV as a vaccine vector.…”
Section: Discussionmentioning
confidence: 56%
“…While EphA2 has been well characterised in the oncogenesis of breast cancer, its association with lesser prevalent cancers such as KS is still being elucidated. So far, EphA2 sequence variations in KS patients have been identified and their functional significance investigated, but the consequences for KS oncogenesis are not yet fully understood [ 82 ]. Therefore, subsequent research into EphA2’s role in KS development is required, which will potentially also shed light on the oncogenic role of EphA2 in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the processes of KSHV infection and KS progression may also have host genetic components to them. Previous work from our laboratory found that EphA2 sequence variants were associated both with KSHV infection and KS prevalence in HIV-infected patients [ 82 ]. These variants were identified in the intracellular and functionally important Pkinase-Tyr and SAM domains.…”
Section: Epha2 Plays a Dual Role In Kaposi’s Sarcoma Oncogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It was further revealed that many amino acids of EPHA2′s LBD are potentially recognized by other γ-herpesviruses, thereby providing the structural basis of EPHA2 recognition by γ-herpesvirus gHgL [ 78 ]. Recently, an investigation of EPHA2 sequence variants in the protein coding region of the gene in South African HIV positive individuals revealed that certain variants, primarily located in the functionally important tyrosine kinase domain, affected patient’s susceptibility to KSHV infection or KS development [ 79 ]. This further supports the current understanding that EPHA2 plays an important role in KSHV entry and may be involved in signaling events leading to KS development.…”
Section: Cell-type Specific Expression Of Surface Receptors Used Bmentioning
confidence: 99%